(untitled) - Haffaf, Renata (Romanica Olomucensia, 2013)
The Islamic city emerges in the modern Spanish prose as a dreamworld or space frozen in time - a result of its idiosyncratic characteristics as well as aesthetic, cultural and ideological factors. While Juan Goytisolo explores the Moroccan cities of Tangier and Marrakech in his novels Count Julian (1970) and Makbara (1980), such a traditional representation is consciously integrated into the narration. At the same time the medina is textually reconstructed, some of its elements become central to the writing, linking its "antiquated" space with the author's understanding of modernity.
Keywords: Morocco in literature; oral literature; urban space; Islamic city; labyrinth; Orientalism.